Oscillometry reference values for children and adolescents - Christoph Valach; Emiel F. M. Wouters; Alina Ofenheimer; Pasquale Pio Pompilio; Alessandro Gobbi; Marie-Kathrin Breyer; Sylvia Hartl; Chiara Veneroni; Tobias Mraz; Caspar Schiffers; Otto Chris Burghuber; Ahmad Karimi; et al. (ERJ Open Research)
Background Oscillometry devices allow quantification of respiratory function at tidal breathing but device-specific reference equations are scarce: the present study aims to create sex-specific oscillometric reference values for children and adolescents using the Resmon PRO FULL device. Methods Healthy participants (n=981) aged 6 to 17 years of the Austrian LEAD general population cohort were included. Subjects had normal weight (body mass index ≤99th percentile) and normal lung volumes (total lung capacity (TLC) ≥ lower limit of normal). Oscillometry data were collected using a single frequency mode of 8 Hz. Sex-specific prediction equations were developed for total, inspiratory and expiratory resistance (R) and reactance (X) as well as for the modulus of impedance (Z) value using the LMS (lambda, mu, sigma) method. Height was used as a single covariate. Results Reference equations for all oscillometry parameters were created for Caucasian children aged 6 to 17 years with a height span from 101 to 183 cm and a lung volume span from 1.7 to 8.8 L TLC. R and Z values progressively decrease and X values increase with increasing height. Oscillometry parameters versus lung volume curves differ from those versus height curves. Stratified for lung size, no sex differences are found for oscillometry parameters. Conclusion Our study provides reference values for oscillometry parameters in children and adolescents using strictly defined criteria for weight and lung volumes. No sex-related differences in oscillometry parameters corrected for height or lung size are found.